Learning Primary Science in a Web-Based Learning Environment - Mohd. Saat, Rohaida (2003)
Learning primary science includes the acquisition of science process skills. Studies have shown that integrated science process skills should be taught through some form of specific training. This study adopts the use of Web-based learning environment in learning science process skills. The purpose of this study was to unravel the learning processes that occurred in the learning of science, particularly the skill of controlling variables, in a Web-based learning environment. The study employed an exploratory qualitative case study which involved nineteen Grade Five children. The participants were selected using the purposive sampling technique. During the study, children explored the specially designed Web-based instructional material known as 'Science Process Skills in Scientific Exploration', in short SPicE. The primary data collection techniques used in this study were interviews, children's conversations, observations, children's diary entries and entries from the on-line discussions. Data from interviews, conversations and observations were transcribed while relevant entries from children's diaries and on-line discussions were extracted. Data were analyzed using the constant comparative method of analysis. The findings of the study suggest that there were three dimensions of learning, the cognitive, interpersonal and intrapersonal dimensions. These learning dimensions were intertwined among each other and were influenced by the design features of SPicE. Besides the acquisition of the intended skills, the findings also indicate that the children acquired other science process skills, manipulative skills as well as computer skills. There were four main factors that influence the acquisition of these skills; the programme, physical setting, the teacher and children's readiness. Three major conclusions were drawn from this study. First, Web-based learning facilitates science learning. Second, besides the intended learning outcome, learners acquired other related skills such as manipulative skills and computer skills, in the Web-based learning environment. Lastly, skill acquisition in the Web-based learning environment is influenced by various external and internal factors.